Development of Public Electric Vehicle Charging Stations (SPKLU) in Makassar as an Electric Car Supporting Means - Nur, Muhammad Yusuf; Nur, Nur Khaerat; Anugrah, Anugrah (Universitas Ibn Khaldun Bogor, 2024)
Electric vehicles are a potential solution for reducing greenhouse gas emissions and dependence on fossil fuels. However, a successful transition to electric vehicles depends on the availability of adequate charging infrastructure. Therefore, this journal aims to describe the development of Public Electric Vehicle Charging Stations (SPKLU) in the city of Makassar, including an analysis of the obstacles, benefits, and steps taken in the development process. This thesis discusses the latest condition of the electric vehicle battery charging infrastructure, especially the electric car General Electric Vehicle Charging Station (SPKLU) located in Makassar. This thesis also discusses the development of electric car sales in Indonesia, especially in the city of Makassar and other cities around it. How to charge electric vehicle batteries either through portable charging, wall charging or charging at SPKLU as one of the supporting infrastructure for electric vehicles. Programs carried out by both the Government and PLN in an effort to encourage people to switch to electric vehicles to reduce air pollution in big cities and also reduce the use of fossil fuels.